Analisis Intensi Isolasi Diri terhadap Perilaku Pembelian Tidak Biasa selama Covid-19 pada Kasus E-Commerce - Disya Intan; Afifah Hasna Auliya (Asosiasi Ahli Administrasi Indonesia, 2021)
During the Covid-19 pandemic, Indonesian were advised to carry out self-isolation intentions The purpose of this study is to find which led to everyone making unusual purchases. Through this background, the purpose of this study is to see the effect of self-isolation on unusual purchasing behavior in e-commerce in Indonesia during the Covid-19 pandemic. From the results of research conducted by researchers using descriptive methods with a quantitative approach, through distribution Questionnaire to 120 respondents, it can be seen that the isolation carried out has a significant effect on unusual purchases (panic buying). This research is expected to provide information, especially for e-commerce so that it can react better to situations in the future.